Frontal damage and resolution of schizophrenia in a patient with self-inflicted gunshot wound: a case report - Shannon Smith; Mayanka Kumar; John Absher (BMC Neurology)
Abstract Background Craniocerebral self-inflicted gunshot wounds (SIGSW) are fatal in 90% of individuals, usually before reaching a hospital setting. We report a unique SIGSW survivor’s residual neurologic deficits, imaging, neuropsychiatric findings, and improvement in psychosis. Case presentation The patient is a 32-year-old right-handed Caucasian male with a medical history of paranoid schizophrenia who attempted suicide by SIGSW. After transport to the Emergency Department (ED), an emergent craniotomy was required for wound debridement, hematoma evacuation, and craniofacial reconstruction. He transitioned to rehabilitation and continued to improve. We evaluated him seven years later when he returned to the ED for breakthrough seizure activity. Detailed neurologic, neurobehavioral, and psychiatric evaluations were accomplished, including the Frontal Assessment Battery (FAB). His deficits included distractibility, impaired digit span, poor confrontation and generative naming, effortful spontaneous speech, and transcortical motor aphasia with frequent semantic paraphasic errors. Language comprehension was intact, and he answered simple questions with short responses. Psychiatric interviews of the patient and his mother revealed resolution of auditory hallucinations and paranoid delusions following recovery from the SIGSW. Discussion Our testing revealed widespread deficits on the FAB. Neurobehavioral and language assessments suggested frontal lobe dysfunction, including transcortical motor aphasia. His psychiatric interview findings revealed similarity to findings report in the 1940s–50s after frontal leukotomy initially proposed by Egas Moniz. Conclusion Frontal lobe damage produced cognitive and neurobehavioral impairments and improved neuropsychiatric symptoms such as hallucinations and psychosis in a SIGSW survivor.